ANALYZING THE RELATIONSHIP BETWEEN COMPENSATION, COMPETENCE, AND WORK ENVIRONMENT WITH EMPLOYEE JOB SATISFACTION AT THE MINISTRY OF TRANSPORTATION - Pitaloka, Anggun; Rangkuti, Zulkifli; Budiraharjo, Joko (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The r test value for the Compensation variable (X1) with rcount is 0.623 and r table for N= 140 is 0.166, significance is 0.000. Because rcount is greater than rtable (0.623 > 0.166 and significance is smaller than 5% (0.000 < 0.050) then Ha is accepted and H0 is rejected, it can be stated that Compensation (X1) is significantly related to Employee Job Satisfaction (Y). The r test value for the Work Competency variable (X2) with an r count of 0.762 and an r table for N= 140 of 0.166 with a significance of 0.000. Because the rcount is greater than r table (0.762 > 0.166 and the significance is smaller than 5% (0.000 < 0.050) then Ha is accepted and H0 is rejected, it can be stated that Compensation (X1) is significantly related to Employee Job Satisfaction (Y), the r test value of the Job Competence variable (X2) with rcount of 0.762 and r table for N= 140 of 0.166 significance of 0.000. Because rcount is greater than rtable (0.762 > 0.166 and the significance is smaller than 5% (0.000 < 0.050) then Ha is accepted and H0 is rejected, it can be stated that Compensation (X1) is significantly related to Employee Job Satisfaction (Y), the ANOVA test value is obtained Fcount is 118,068 while Ftable (a 0.05) for n = 136 is 2.44. So Fcount > from Ftable (a 0.05) or 140,753 > 2.44, with a significance level of 0.000 because 0.000 < 0.05, it can be said that Compensation (X1), Work Competence (X2) and Work Environment (X3) together are related to Employee Job Satisfaction (Y), the correlation coefficient is 0.850 and According to the provisions, these four variables have a positive relationship. This means that the variables Compensation (X1), Work Competence (X2) and Work Environment (X3) have a very strong positive relationship with Employee Job Satisfaction (Y)